A health risk assessment of the heavy metal levels in soil from Itagunmodi and Iperindo mining belt, Southwest Nigeria - Kugbere Emumejaye; Enyioma C. Okpara; Morohufoluwa A. Olaoye; Sakirudeen A. Ishola; Peter E. Biere; O. A. Mustapha; Craig E. Banks; Damian C. Onwudiwe; Victor Makinde; A. M. Gbadebo (Discover Environment)
Abstract Artisanal and small-scale gold mining activities have raised significant environmental and public health concerns in Osun State, Nigeria, due to the accumulation of heavy metals in soil. This study assessed the concentrations of heavy metals in soil samples from two major mining sites, Itagunmodi and Iperindo, and evaluated the potential health risks posed to local miners. Soil samples were systematically collected and analysed using particle-induced X-ray emission (PIXE) spectroscopy. Concentrations of arsenic, lead, chromium, mercury, copper, zinc, and nickel were quantified, and statistical analyses were employed to determine inter-site differences. Health risk assessments, based on USEPA models, estimated both non-carcinogenic (hazard index) and carcinogenic risks (excess lifetime cancer risk) through ingestion, inhalation, and dermal exposure pathways. The results showed significantly elevated concentrations of Pb, As, and Cr, particularly in Itagunmodi, with cancer risk values (2.90E−4 for Itagunmodi and 2.31E−4 for Iperindo) exceeding the acceptable USEPA threshold (1.0E−6 to 1.0E−4). Non-cancer risks were also highest through the ingestion pathway. These findings highlight the urgent need for targeted remediation, policy intervention, and public health education to mitigate exposure in mining communities and promote sustainable mining practices.